Profile study of ectopic pregnancy at Department of Obstetrics and Gynecology, Dr. Soetomo Hospital, Surabaya, Indonesia - Andarisa Rachman Nugraha; Ashon Sa’adi; Ni Wajan Tirthaningsih (Majalah Obstetri dan Ginekologi, 2020)
Objective: Ectopic pregnancy is a leading cause of maternal death during the first trimester of pregnancy, it can cause infertility and even death as a result of massive bleeding of the mother. Based on those fact, study of ectopic pregnancy is needed.Materials and Methods: This study used retrospective design and total sampling to collect the data and present it as a descriptive – analytical result.Results: Of the 98 samples, as many as 30.6% of the patients age was in the range of 26 - 30 years, there was 16.3% of patients with unmarried status, hormonal contraception was more often used by patients than intrauterine device, there were 7% of patients with recurrent ectopic pregnancy, as many as 12.1% of patients had a history of surgery in the abdomen or pelvic area, ectopic pregnancy was most common in first pregnancies, and there were 26.4% of patient found with Infection.Conclusion: Ectopic pregnancy has many risk factors, Ectopic pregnancy could be cause by solely one risk factor or more (multifactorial), The most commonly found risk factor was infection.